2013
DOI: 10.1007/s11748-013-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement in an elderly patient with factor XI deficiency

Abstract: Factor XI (FXI) deficiency is rare and associated with bleeding after surgical procedures. We report a case of an 80-year-old woman with severe aortic valve stenosis. FXI deficiency was diagnosed due to prolonged activated partial thromboplastin time. Aortic valve replacement was performed using a porcine bioprosthetic valve. Intra-operation bleeding was controlled by the transfusion of a fresh frozen plasma. The postoperative course was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Avci et al 10 used recombinant factor VIIa to control bleeding during mitral valvuloplasty in a 4.5‐year‐old patient with congenital FXI deficiency and reported no major postoperative bleeding. Watanabe et al 11 reported the use of fibrin glue and tranexamic acid infusion without FFP replacement or factor concentrate infusion to manage bleeding during aortic valve replacement, regardless of the preoperative aPTT of 106 seconds. They noted that the bleeding was controlled only after FFP replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Avci et al 10 used recombinant factor VIIa to control bleeding during mitral valvuloplasty in a 4.5‐year‐old patient with congenital FXI deficiency and reported no major postoperative bleeding. Watanabe et al 11 reported the use of fibrin glue and tranexamic acid infusion without FFP replacement or factor concentrate infusion to manage bleeding during aortic valve replacement, regardless of the preoperative aPTT of 106 seconds. They noted that the bleeding was controlled only after FFP replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA and Japan, the only replacement therapy is FFP. 6 There have been no reports of FXI concentrate used for treatment of FXI deficiency in a patient undergoing AVR. We used Hemoleven as the replacement therapy of choice because it prevents massive bleeding perioperatively.…”
Section: Discussionmentioning
confidence: 99%
“…8 Of the 10% of patients treated with FXI concentrate who developed arterial thrombosis or venous thromboembolism, almost all were predisposed to thrombosis, elderly, and had cardiovascular disease. 6 Routinely, our patient received acenocoumarol and enoxaparin.…”
Section: Discussionmentioning
confidence: 99%
“…7 Two case reports described the management of FXI deficiency in the setting of aortic valve replacement. 8,9 One patient was managed successfully with FFP and tranexamic acid and the other with FXI concentrates without excessive bleeding. A paediatric case described a 4.5-year-old male with FXI deficiency underwent a mitral valvuloplasty that was supported with nine serial doses of rFVIIa at 90 mcg/kg IV without excessive perioperative bleeding 13 .…”
mentioning
confidence: 99%